Mischung: Possible! Experimentelle Quartiersentwicklung am Beispiel Nordbahnhof Wien - Peer, Christian; Forlati, Silvia (De Gruyter, 2022)
Mischung: Possible! offers basic knowledge on mixed-use planning based on a case study of an urban development project. The scenarios include mobility, care work, zero emissions, the sharing economy, creative clusters, "fair business," networked services, and urban manufacturing. The goals are to deliver both collective and individual added value and to develop innovative buildings in an "urban base."